Maltreatment timing, HPA axis functioning, multigenic risk, and depressive symptoms in African American youth: Differential associations without moderated mediation. (December 2020) - VanZomeren, Adrienne A.; Zhang, Jingchen; Lee, Sun-Kyung; Gunlicks-Stoessel, Meredith; Piehler, Timothy; Cicchetti, Dante
Abstract: Utilizing a large ( N = 739), ancestrally homogenous sample, the current study aimed to better understand biological risk processes involved in the development of depressive symptoms in maltreated, African American children age 8-12 years. Maltreatment was independently coded from Child Protective Services records and maternal report. Self-reported depressive symptoms were attained in the context of a week-long, summer research camp. DNA was acquired from buccal cell or saliva samples and genotyped for nine polymorphisms in four hypothalamic-pituitary-adrenal (HPA)-axis-related genes: FKBP5, NR3C1, NR3C2, and CRHR1 . Salivary cortisol samples were collected each morning (9 a.m.) and late afternoon (4 p.m.) throughout the week to assess HPA functioning. Results revealed that experiences of maltreatment beginning prior to age 5 were most predictive of depressive symptoms, whereas maltreatment onset after age 5 was most predictive of HPA axis dysregulation (blunted daytime cortisol patterns). Multigenic risk did not relate to HPA functioning, nor did it moderate the relationship between maltreatment and HPA activity. There was no mediation of the relationship between maltreatment and depressive symptoms by HPA dysfunction. Results are interpreted through a developmental psychopathology lens, emphasizing the principle of equifinality while carefully appraising racial differences. Implications for future research, particularly the need for longitudinal studies, and important methodological considerations are discussed.